2019
DOI: 10.14444/6031
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Radiological Outcomes of Combined Anterior-Posterior Approach Versus Posterior Alone in Management of Isthmic Spondylolisthesis. A Systematic Review and Meta-Analysis

Abstract: Background: Lumbar isthmic spondylolisthesis (IS) in adults is defined as the forward slippage of a vertebra onto the top of the vertebra, resulting from a defect in the pars intraarticular, and can be low grade or high grade. Persistent back pain or neurological deficit are indications for surgical intervention. Surgery can be done from back, front, or both, with or without fusion, instrumentation, or decompression, and short or long segment. Methods: Following the Preferred Reporting Items for Systematic Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
3
25
1
Order By: Relevance
“…Our satisfactory outcome rate (91%), fusion rate (100%), and complication rate (9%) were similar to those of studies in which low-grade spondylolisthesis was treated with ALIF alone or ALIF with posterior instrumentation. In our study, the fusion rate (100%) is relative high among the similar studies [ 10 13 , 41 ]. The reason may be that all of our cases undergone posterior instrumentation.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our satisfactory outcome rate (91%), fusion rate (100%), and complication rate (9%) were similar to those of studies in which low-grade spondylolisthesis was treated with ALIF alone or ALIF with posterior instrumentation. In our study, the fusion rate (100%) is relative high among the similar studies [ 10 13 , 41 ]. The reason may be that all of our cases undergone posterior instrumentation.…”
Section: Discussionsupporting
confidence: 54%
“…In order to attain the abovementioned advantages, some authors advocated ALIF and percutaneous pedicle screws to treat isthmic spondylolisthesis [ 10 12 ]. Though good to excellent results have been reported, to date, the application of ALIF is still limited in the treatment of low-grade lumbar spondylolisthesis [ 11 13 ].…”
Section: Backgroundsmentioning
confidence: 99%
“…Various studies have reported that the surgical treatment of isthmic spondylolisthesis significantly improves functional outcomes 1,7,16) . Through many years of follow-up on surgically treated spondylolytic patients, numerous studies described the surgical results and degeneration of adjacent segments to fused vertebrae 2,23,29) .…”
Section: )mentioning
confidence: 99%
“…Nonoperative management tends to be considered for minimally symptomatic or asymptomatic adolescents with low-grade spondylolisthesis (12). At the same time, surgical treatment provides a better outcome for those who are unresponsive to conservative therapy, such as individuals with high-grade spondylolisthesis, continual symptomatology, or neurological deficits (13)(14)(15)(16). In terms of surgical management, arthrodesis has shown to be effective for lumbar spondylolisthesis (17), but consensus has yet to be reached on whether reduction or arthrodesis in situ is the more suitable technique for adolescent spondylolisthesis.…”
Section: Introductionmentioning
confidence: 99%